Novel Probiotics and Prebiotics: How Can They Help in Human Gut Microbiota Dysbiosis? - Gallego Carlos Gomez; Salminen Seppo (SHAHID BEHESHTI UNIV MEDICAL SCIENCES, 2022)
Background and Objectives: Novel probiotics and prebiotics designed to modulate the gut microbiota for improving health outcomes are in demand as the importance of the gut microbiota in human health is revealed. A review of the scientific literature regarding the current knowledge and novel species and novel oligosaccharides for the treatment of dysbiosis-associated diseases has been carried out due to their growing interest.
Results and Conclusions: The regulations governing introduction of novel probiotics and prebiotics vary by geographical region. Novel foods and foods with health claims fall under specific regulations in several countries. In European Union (EU), safety is assessed by novel food approval process and by the European Food Safety Authority (EFSA) established Quantitative Presumption of Safety (QPS) system for bacteria and other biologicals. Any messages on health benefits are covered by the European Regulation on Health Claims (ERHC), also assessed by EFSA. Examples of recent novel probiotics in EU include Clostridium butyricum, and Bacteroides xylanisolvens and examples of novel prebiotics include human milk oligosaccharides such as Lacto-N-neotetraose. Yacon root is an example on a previously novel prebiotic food which is allowed due to the reported existing cultivation and use in EU prior to the novel food regulation. Potential future candidates include further human milk oligosaccharides and bacteria such Faecalibacterium prausnitzii and Akkermasia muciniphila. Increasing knowledge on human intestinal microbiota and microbiota development enables the design of new more specific and hitherto unknown probiotics and prebiotics. Also understanding the microbe and microbe host interactions facilitates the search for novel probiotics and prebiotics.